Pemahaman Kekerasan Terhadap Anak Dalam Perspektif Hadis Nabi - Saein Ervana (IAIN Purwokerto, 2022)
This paper is focused on answering basic questions about violence against children in the perspective of the Prophet's Hadith. The hadith that is used as the main footing is the Hadith of the history of Sunan Abu Daud number 418 about hitting children. through the Hadith, the analysis will be carried out starting from the elaboration of the Syarah Hadith and contextual understanding of the Hadith hitting the child. Based on the target, the research method used in this study is qualitative with the type of library research. The datacollection technique used by the researcher is the Takhrij Hadith method. In this context, the data analysis technique used in this study uses an analytical model which includes data collection, data reduction, data presentation, and drawing conclusions or verification. Of the six important dimensions of violence mentioned above, the violence as contained in the Hadith narrated by Sunan Abu Daud 418 is included in the form of physical and psychological assertiveness, namely hitting children. Based on the analysis above, it can be concluded that the understanding of violence towards children in the Hadith perspective is oriented to three things, namely assertiveness as a form to condition children to be responsible, assertiveness as a form to condition children into discipline, andassertiveness as a form of conditioning children to be polite.Of these three things, assertiveness towards children can only be done depending on the situation and conditions itself